0916 The Use of Immersive Virtual Reality and Slow Breathing to Enhance Relaxation and Sleep in Adolescents. (27th May 2020) - Yüksel, D; Goldstone, A; Prouty, D; Forouzanfar, M; Claudatos, S; Lee, Q; Wang, R; Dulai, T; Arra, N; Volpe, L; Durley, I; Baker, F; et al.
Abstract: Introduction: Sleep disturbances frequently emerge during adolescence amongst profound, normative, sleep maturation and biopsychosocial changes. Factors like stress, worry or rumination may make falling asleep and maintaining sleep more difficult. Here, we evaluate the efficacy of a novel intervention based on virtual reality (VR) and slow breathing to promote bedtime relaxation and facilitate sleep in high-school adolescents. Methods: Twenty-nine 16-18 year-old adolescents with (N=9, 6 girls) and without (N=20, 11 girls) sleep difficulties underwent two counterbalanced in-lab relaxation and baseline polysomnography (PSG) nights. For the relaxation condition, immediately preceding bedtime, participants were engaged in slow diaphragmatic breathing (to promote physiological downregulation) whilst passively experiencing a relaxation immersive VR environment, designed to promote cognitive relaxation/distraction (20min). On the baseline night, participants engaged in quiet activities (e.g., reading a book) before bedtime (20min). Results: The VR intervention resulted in a significant immediate increase in perceived relaxation and reduced worry (p<0.05). Also, heart rate dropped ( 5bpm) in the pre-to-post intervention (p<0.05), while no significant change in heart rate was evident before and after the time spent in quiet activities on the baseline night. PSG-defined sleep onset latency was shorter ( 6min reduction) and sleep efficiency was greater ( 3% increase) on the VR relaxation night compared to the baseline night (p<0.05). In addition, baseline sleep onset latency was related to the magnitude of the baseline-to-relaxation reduction in sleep onset latency in participants (R 2 =0.70; p<0.01). There was no apparent difference in responses to the VR intervention between adolescents with or without insomnia. Conclusion: Our data highlight the potential for combining cognitive relaxation/distraction strategies, using immersive VR technology and physiological downregulation, to promote bedtime relaxation and improve overall sleep quality in adolescents. Further research is needed to evaluate the feasibility and effectiveness of such interventions over time. Support: National Heart, Lung and Blood Institute (NHLBI) R01HL139652 (to MdZ)